2014
DOI: 10.1094/mpmi-03-14-0090-r
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Xylella fastidiosa RpfF in Citrus Disrupts Signaling in Xanthomonas citri subsp. citri and Thereby Its Virulence

Abstract: Xylella fastidiosa and Xanthomonas citri subsp. citri, that cause citrus variegated chlorosis (CVC) and citrus canker diseases, respectively, utilize diffusible signal factor (DSF) for quorum sensing. DSF, produced by RpfF, are similar fatty acids in both organisms, although a different set of genes is regulated by DSF in each species. Because of this similarity, Xylella fastidiosa DSF might be recognized and affect the biology of Xanthomonas citri. Therefore, transgenic Citrus sinensis and Carrizo citrange pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Few studies have introduced bacterial genes into crops to combat Xanthomonas diseases in greenhouse conditions. For example, Caserta and colleagues have introduced DSF producing gene rpfF from Xylella into citrus and demonstrated enhanced resistance to X. citri, possibly through misregulation of virulence-associated genes in an improper bacterial quorum (Caserta et al 2014). In addition, Zhang and colleagues expressed Pantoea albD, which was shown to detoxify the X. albilineans toxin albicidin in sugarcane.…”
Section: Introduction Of Resistant Varieties Through Genetic Engineeringmentioning
confidence: 99%
“…Few studies have introduced bacterial genes into crops to combat Xanthomonas diseases in greenhouse conditions. For example, Caserta and colleagues have introduced DSF producing gene rpfF from Xylella into citrus and demonstrated enhanced resistance to X. citri, possibly through misregulation of virulence-associated genes in an improper bacterial quorum (Caserta et al 2014). In addition, Zhang and colleagues expressed Pantoea albD, which was shown to detoxify the X. albilineans toxin albicidin in sugarcane.…”
Section: Introduction Of Resistant Varieties Through Genetic Engineeringmentioning
confidence: 99%
“…fastidiosa and Xcc has indicated that DSF signaling is normally finely balanced during the disease process and that such a fine balance might therefore be readily disrupted by either degradation or over-production of the signal, with consequences for disease control [ 31 ]. One approach has been to engineer plants to express RpfF and hence elevate DSF levels [ 47 , 48 ]. Plant expression of RpfF from X .…”
Section: Establishment Of Methods For Interference With Dsf Family Simentioning
confidence: 99%
“…fastidiosa and X. citri , respectively, (Caserta et al . ; Lindow et al . ) although the underlying mechanisms are not fully understood.…”
Section: Control Of Bacterial Phytopathogenesis By Overexpression Of mentioning
confidence: 99%
“…fastidiosa in grape and citrus reduces the virulence of Xy. fastidiosa and X. citri, respectively, (Caserta et al 2014;Lindow et al 2014) although the underlying mechanisms are not fully understood. RpfF expression in grape directs the production of XfDSF as well as XfDSF2 .…”
Section: Control Of Bacterial Phytopathogenesis By Overexpression Of mentioning
confidence: 99%